Technology Education Challenges and Solutions in Latin America - Jordán, Ramiro (2001)
The world has become dependent on informa-tion, technology, and telecommunications, better known as Information Technology and Telecommunications (IT&T), a term that encompasses the fields of Electrical and Computer Engineering, and Computer Science. Increasingly, IT&T is an effective indicator of the difference between developed and developing nations. The competitiveness of a nation is directly related to its incorporation of IT&T which requires a substan-tial restructuring of the forms and procedures in attempting to generate a base for development of science and technology. To achieve this, it is important to revise the education of human technical and scientific resources. This paper summarizes the experience of the Ibero-American Science and Technology Edu-cation (ISTEC) consortium in IT education in Latin America.